Integrating the contribution of museums for building peaceful and inclusive society and promoting justice - Li Xiang; Tanot Unjah; Sharina Abdul Halim (Discover Sustainability)
Abstract Within the literature concerned with museums’ contributions to the United Nations Sustainable Development Goals, the most studied museums’ focus was on Goals 8 and 11, which promote decent work, economic growth and the sustainable development of cities and communities. Moreover, museums also play a crucial role in supporting Goal 16 by ensuring public access to information and protecting fundamental freedoms following national legislation and international agreements. However, the museums' contribution to SDG 16 achievement has often been omitted. This paper presents a specific study investigating the approaches, methods and tools being deployed in managing museums in collaboration with institutions at all levels. The study is based on a systematic literature analysis and field data collection from a cultural project “Carp Leaping Over Dragon’s Gate”. Cases corresponding to museum theories and practices as well as relevant projects have been critically analyzed and studied. The research findings include the set targets, the implemented projects that allow for building a peaceful and inclusive society and promoting justice for all in museums, and the ways they help achieve SDG 16. Hence, the paper will bring a completely new meaning to the mission of museums as more dynamic institutions committed to the achievement of SDGs.